The European economic integration and the globalisation process: a preliminary discussion - Mendonça, António (2004)
In May 2004 ten more countries, mainly from Central and Eastern Europe, will join the European Union increasing to twenty-five the total members of the group. This enlargement, however, was not followed by significant progresses on the integration level deepening. On the contrary, we saw the evolution to higher forms of economic and political integration enter a period of stagnation or, even, regression, in spite of the need for accommodation the more complex administration of the twenty five Union affairs. Two major events gave substance to this contradiction between the enlargement process — this time rather significant, both in geographical and population terms — and the deepening process of the integration levels.